Análisis del comportamiento de las remesas enviadas a Ecuador al momento actual - Villamar Lliguicota, Leslie Renata (2022)
The results presented correspond to the research project Analysis of the behavior of remittances sent to Ecuador at the present time, so that the general objective of analyzing the behavior of remittances has been achieved, through the development of specific objectives aimed at the systematization of theories, characterization of historical behavior and determination of discrete ways for a better use of remittances. To this end, a descriptive and bibliographic documentary research methodology was put into practice based on a mixed approach, since from the qualitative point of view, conceptual generalizations were reached in addition to the application of the structured interview that provided coincidental information on remittances; on the other hand, the statistical method was used for the purposes of data processing, presentation and analysis, which evidences the quantitative edge of the approach............